Identification of practices and morbidities affecting the mortality of very low birth weight infants using a multilevel logistic analysis: clinical trial or standardisation?. Issue 8 (21st August 2013) - Kusuda, Satoshi; Fujimura, Masanori; Uchiyama, Atsushi; Nakanishi, Hidehiko; Totsu, Satsuki; ,
Abstract : Objectives: To determine the feasibility of clinical trials of newly developed treatments or standardisation of existing practices to further improve outcomes among very low birth weight (VLBW) infants, a nationwide database was analysed with a two-dimensional approach using two multivariate logistic models. Design: Retrospective observational analysis. Setting: Level III perinatal centres in Japan. Participants: 15 920 VLBW infants admitted at 38 participating centres from 2003 through 2010. Outcome measures: Clinical information for the infants was collected until discharge from the centres. A multivariate logistic model identified practices and morbidities associated with mortality. Then, those which were significantly associated with mortality were analysed using a multilevel logistic model. The residues calculated by the multilevel analysis were used as an indicator of centre variation. Results: Among practices, antenatal steroids and intubation at birth showed relatively high centre variations (0.9 and 0.8) and favourable ORs (0.7 and 0.5) for mortality, while caesarean section showed a low centre variation (0.4) and a favourable OR (0.8). Sepsis and air leak showed high centre variations (0.4 and 0.4) and high ORs (3.8 and 3.4) among morbidities. Pulmonary haemorrhage, persistent pulmonary hypertension of the newborn, and intraventricular haemorrhage showed moderate variations (0.2, 0.3 and 0.2, respectively) and high ORs (5.6, 4.1 and 2.9, respectively). In contrast, necrotising enterocolitis showed the lowest variation (0.1) and a high OR (4.9). Conclusions: The two-dimensional approach has clearly demonstrated the importance of clinical trial or standardisation. The practices and morbidities with low centre variations and high ORs for mortality must be improved through clinical trials of newly introduced techniques, while standardisation must be considered for practices and morbidities with a high centre variation. Trial registration: The database was registered as UMIN000006961.